Greek Foreign Policy at the Turn of the Millennium - Chrysanthopoulos, Leonidas (Études helléniques / Hellenic Studies, 2002)
This text is adapted from a lecture given at Concordia University, on June 6, 2001, organized by the Centre of Hellenic Studies and Research Canada-KEEK. A revolution took place in Greek Foreign Policy in 1981 when Greece joined the EU (then called the EEC). It was in that year that Greece had to depart from her egocentric foreign policy and was obliged to formulate, within European Political Cooperation (EPC), policies on Asia, Africa, South America. Whenever the EU was to make a policy statement or issue a declaration, for exarnple decisions on the situation in El Salvador, Namibia and Laos, Greece had to participate in the formulation of such a policy by taking a position during the drafting exercises. We had to explain to our Ministers, the national considerations behind an EU position which meant that we had to study and scrutinize the internai situation in El Salvador, Namibia or Laos. The same applied to the preparation of the EU speech at the annual General Assembly. It was at this point that Greece started to learn in detail about the domestic problems of the rest of the world and became involved in solving them. This is simply the general background to the discussion at hand on bilateral relations berween Greece and Canada. The article will also describe Greece's present foreign policy.